House price prediction using daily news data - Sara J. Kirkeby; Vegard Høghaug Larsen (Norges Bank, 2021)
We investigate whether information from news articles could improve predictions of house price inflation at a short forecast horizon. The Covid-19 pandemic led to a shutdown of the Norwegian economy on March 12th 2020. Large economic fluctuations posed challenges for models used to forecast economic developments. Our results indicate that news data contain valuable information about the direction of the housing market in periods of economic distress.
hdl:11250/2760504
Keywords: 330; Immobilienpreis; Inflation; Prognoseverfahren; Norwegen